Determinant of financial performance for family takaful in Malaysian industry / Intan Nur Syafinaz Saiful Bahri - Saiful Bahri, Intan Nur Syafinaz (2012)
Malaysia's Takaful industry is a developing rapidly since the first Takaful Company which is Syarikat Takaful Malaysia was established in 1985. Since year 2005 until 2010, the Malaysian Takaful has been experiencing the increasing and Family Takaful business shows the positive growth. The aim of this study is to analyze the factor that influencing financial performance of Family Takaful business. This study is limited to focus in 8 years period. Financial data has been collected on yearly basis from year 2003 until year 2010. 8 Takaful operators out of 12 has become as a sample. Data analysis has been done by using Eviews program. The data collected was analysed by using a basic statistical techniques which is Multiple Linear Regression. The result shows that the Company Size has a significance negative relationship with the financial performance of Malaysian Family Takaful. Meanwhile, Liquidity and Underwriting Risk have a significant positive relationship with the financial performance of Malaysian Family Takaful.